Contamination, potential mobility, and origins of lead in sediment cores from the Shima River, south China. (November 2018) - Gao, Lei; Li, Shaoheng; Wang, Zhuowei; Liang, Zuobing; Chen, Jianyao; Liang, Bin
Abstract: Identifying contamination sources of environmental media and revealing their changing trends over time is useful for regional contamination control and environmental improvements. Four sediment cores (S1−S4) were collected from the Shima River to determine lead (Pb) concentrations, geochemical fractions and isotopic compositions, as well as the geochronology of core S3. The results show that Pb concentrations decreased from the upper and middle reach sites (means: 57.6, 95.9, and 97.6 mg kg −1, respectively) to the lower reach site (43.8 mg kg −1 ), resulting in a minimal to moderate enrichment in the sediments; enrichment increased due to anthropogenic Pb inputs at the river middle reach site since the 1990s. Sediment Pb in the geochemical fractions followed a decreasing order of reducible (47.3%) > residual (37.8%) > oxidizable (11.2%) > acid-soluble fraction (3.68%), exhibiting high mobility, further verifying the anthropogenic inputs. A descending trend in the 206 Pb/ 207 Pb ratio of the top sediments was the result of anthropogenic activities. In the present study, coal combustion, which was the major anthropogenic Pb source determined by its isotopic composition, contributed significantly (means: 18.4–60.6%) to sediment Pb based on a three end-members model. Less of a contribution (0–10.6%) was derived from vehicle exhaust. The increasing trend in the coal contribution was in accordance with that of the coal consumption in the study area. These results suggest that Pb contamination resulting from coal combustion has grown to become a major environmental issue in the study area. Graphical abstract: Image 1 Highlights: 30-year pollution history of sediment Pb was reconstructed in an urbanized watershed. EFs of Pb indicated an increasing enrichment at the middle reach site since 1993. Mn hydro (oxides) were found to be the major sink for anthropogenic Pb. Coal consumption contributed more significantly than vehicle exhaust to sediment Pb. Abstract : Coal combustion was identified as the major anthropogenic Pb source, with a more significant contribution than that of vehicle exhaust, to the enrichment of Pb in sediments from the Shima River.